Imipenem-associated seizure in a patient operated for left-sided colon tumor (Annals of Medical Research, 2021)
Although the pathophysiology of drug-associated seizures involves many factors, it mainly depends on the culprit drug and case-specific factors. There is usually no previous history of epilepsy in these patients, and epileptic seizures are due to lowering in epileptic threshold by the culprit drug. Epileptic seizures usually do not recur when the culprit agent is discontinued. Convulsion is a rare side effect of beta-lactam antibiotics. The neurotoxic side effects of carbapenem group antibiotics are thought to occur through an interaction with amino butyric acid receptors. Meropenem and imipenem are also a carbapenem group antibiotic. A 61-year-old man who developed a postoperative wound infection after being operated for left colon tumor had Klebsiella Pneumoniae proliferation in culture antibiogram and was put on imipenem/cilastatin treatment. He developed seizures with tonic-clonic convulsions on the fourth day of treatment, and the seizures were attributed to the imipenem/cilastatin treatment. No other pathology suggestive of seizure etiology could be found in his examinations. His antibiotic regimen was changed to a different one and he was discharged in good health on the 11th day of his hospital admission.
Keywords: Antibiotheraphy; Imipenem; Seizure.